Promotion Using Product Placement in Movies: Perception of Rural and Urban Indian Audience - Choubey, Vardhan; Bumb, Riddhi (Indian Journal of Marketing, 2013)
Product placement as a promotional tool is often used as an alternative by marketers. Not much focus is placed on this tool. The present paper discusses concepts related to product placement. The paper highlights the importance of product placement as a promotional tool. It has implications for marketers and researchers. Initially, the literature was reviewed to understand the concepts and findings in product placement. It was found that not much work is done in India on product placement. The study intends to capture the perceptual differences of rural and urban consumers. The differences in perception were studied on the basis of certain factors. The responses were obtained from urban and rural consumers near Indore, Madhya Pradesh, and independent sample t-test was used to study the significant differences. Results show that both rural and urban consumers are influenced by products placed in movies. However, the urban consumers were more interested in buying the products used in movies than the rural consumers.